Architectures of Appropriation: Salvage, Repatriation, and the Politics of Jean Prouvé's Maisons Tropicales. Issue 1 (1st July 2022) - Treier, Leonie
Abstract: The Maisons Tropicales are three prefabricated housing structures designed by Jean Prouvé. Fabricated in France, they were transported to and assembled in Brazzaville and Niamey, then part of the French colonies, around 1950. Their design was tied closely to the belief in the so-called civilizing and enlightening power of European modernist design and, thereby, also the French colonial agenda. In the early 2000s, an American collector, Robert Rubin, and a French art dealer, Eric Touchaleaume, "repatriated" the houses to France. There, they were transformed into and celebrated as icons of French modern design, while their colonial histories were ignored. This article analyzes the importance of discourse in this transformation and how it reflects ongoing dynamics of power and dispossession in the art world. Rubin and Touchaleaume simultaneously employed conflicting narratives mirroring anthropological "salvage" and "repatriation" discourses to describe the Maisons' removal. The case study highlights the moral weight associated with the language around processes of repatriation, the nested relationships between heritage and the market, and the continuation of colonial practices of dispossession.